RENTAL APPLICATION PROGRAM DESIGN DVD RENTAL 'MYDISC "USING MICROSOFT VISUAL BASIC 6.0 - Su warno; Erick Orlando, SKom., MMSI (Jurnal Sistem Informasi, 2007)
In this scholarly writing explain about the making of the DVD leasing application program by using Visual Basic 6.0 programs consist of the login form Main Menu, the form customer, the form Rental Transactions and Customer Reports form can be printed.       Then, making this application utilizing Microsoft Access database on the facilities and work under windows operating system to facilitate in making this program       Lease is an agreements in which the tenant must pay or provide compensation or benefits from the objects or goods owned by the owner of the loaned items. Example of a lease in everyday life such as office building contract hire, lease land for agricultural land, hire / charter vehicles, rentals vcd and dvd original, and etc.